Komunikasi Persuasif Prajuru Desa Pakraman Dalam Pelestarian Kesenian Makepung Di Desa Pakraman Baluk Kecamatan Negara Kabupaten Jembrana - Ade Meila (Jurnal Penelitian Agama Hindu, 2019)
Makepung art is an art and cultural attraction, prajuru Pakraman village is very concerned with the artistic traditions such as makepung in Jembrana Regency so that ways are sought to maintain the preservation of the makepung art. This is intended to maintain and preserve the existence of makepung which has become a characteristic of Jembrana Regency and bring a lot of income to Pakraman Baluk Village as well as increase income for the community. Based on this background, three problems can be formulated, namely (1) What is the persuasive communication process of Pakraman Village Prajuru in the preservation of Makepung art? (2) What factors inhibit persuasive communication of Pakraman Village Prajuru in preservation of Makepung art in Pakraman Baluk Village, Negara District, Jembrana Regency? (3) What efforts have been made in the persuasive communication of Pakraman Village teachers in the preservation of makepung art? The research objective is the general purpose to be able to contribute ideas about how the persuasive communication process of Pakraman village prajuru in preservation of makepung art in Pakraman Baluk Village, Negara District, Jembrana Regency. Specific purpose is to find out the persuasive communication process of Pakraman Village teachers in the preservation of makepung art in Pakraman Baluk Village, Negara District, Jembrana Regency. This research uses Persuasive Communication Theory, Communication Obstacle Theory, and Structural Functional Theory. This type of research is qualitative research with data collection techniques used namely observation, interviews, literature and documentation. Data analysis is presented in descriptive qualitative. This study found that the process of persuasive communication from prajuru as a communicator, to influence, in achieving the objectives achieved by communication using. Interpersonal Communication, Group Communication, Mass Communication, with Informative Communication Techniques and Instructive or Coercive Communication Techniques. Factors that hinder persuasive communication of Pakraman village teachers are mechanical and semantic disturbances of interest, interest, prajuru motivation. Pakraman village is able to establish harmonious relationships within and outside the organization, especially building public trust (village manners) in preserving the role of village prajuru as leaders. protect the community capable of giving information to the community. As a communicator in the preservation of makepung the efforts made are to optimize the persuasive communication of the village of Pakraman Baluk, the socialization of the importance of preserving the makepung art by holding Dharma Wacana, Tula Dharma and activities in the preservation of makepung art.